Cariotipo de Planococcus minor (Homoptera: Coccidae) - Pupo, H. E.=700 1 Martínez, M de los A.; Carballo, N.
Resumenes (Es, En)
10 ref.
Keywords: PLANOCOCCUS; CARIOTIPOS; PARTENOGENESIS; PLANOCOCCUS MINOR